HUBUNGAN ANTARA REGULASI EMOSI DENGAN PARENTAL SELF-EFFICACY PADA IBU ANAK PRASEKOLAH KB-TK ‘AISYIYAH DI SIDOARJO - Asyifa Qulubiyah; Widyastuti - (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study is motivated by the phenomenon of parental self-efficacy. Many school children have maladaptive behavior so parents must have the ability to care for their children. The purpose of this study was to determine whether there is a relationship between emotion regulation and parental self-efficacy of preschool mothers of KB-TK 'Aisyiyah in Sidoarjo. This study used a correlational quantitative method. The population was 205, namely mothers who have preschool children aged 3-6 years old at KB-TK 'Aisyiyah in Sidoarjo. Determination of the sample using saturated sample technique where the entire population is used as a research sample. The data collection technique in this study used a psychological scale in the form of a questionnaire. The data analysis technique used in this study is product moment correlation using JASP 0.16.20. The results showed that the correlation coefficient = 0.213 with a significance of 0.003 <0.05. These results mean that there is a positive relationship between emotion regulation and parental self-efficacy. Thus, the hypothesis proposed in this study is accepted, the higher the emotion regulation, the higher the parental self-efficacy owned, on the contrary, the lower the emotion regulation, the lower the parental self-efficacy owned.